RESEARCH DATA ON THE PREVALENCE OF HEPATITIS C VIRUS ANTIBODIESAMONG INPATIENTS AT A HOSPITAL IN CENTRAL BULGARIA: 2021 –2022 - A.Gotseva; E.Naseva (Trakia Journal of Sciences)
Introduction and purpose: Hepatitis C Virus (HCV) infection is a leading cause of chronic liver diseases including cirrhosis and hepatocellular carcinoma. There is insufficientdata onthe prevalence of HCV among hospitalized patients. Targeted testing for anti-HCV is an effective strategy for identifying asymptomatic infected individuals. The purposeof the present study was topresent the results of screening for anti-HCV among inpatients ata hospital in Central Bulgaria.Methods: A total of 3275 serum samples from 1968 men and 1307 women were tested for presence of anti-HCV atthe Laboratory of Virology within theMultidisciplinary Hospital for Active Treatment (MHAT) “Uni Hospital” (Panagyurishte, Bulgaria) in the period 2021-2022. Serological analysis based on theELFA method was performed using VIDAS Anti-HCV automated test (BioMerieux, France). Results: Thirty-two of the tested patients (1.0%; 95% CI 0.6%-1.3%) wereHCV positive. The difference between the numbers of the hospitalized (n=29) and the outpatients (n=3) wasnotable. The sex distribution shows that 53.1% weremen and 46.9% werewomen. Their median age was67 years (IQR 56-75), as the involvement of the age group 60-79 years (n=16) waspredominant. A total of eight patients were diagnosed with hepatic cirrhosis, whereasthree more patients hadhepatocellular carcinoma. Conclusions: We found a low level of the prevalence ofanti-HCV (1%) among the patients of MHAT “Uni Hospital”, which is analogous to the level reported in the general population. We detected a higher incidence of HCV-positive serostatus among the older in comparison to younger age groups. Timely diagnosis and referrals to a gastroenterologist help to avoid progression of liver damage. All viremic patients (HCV RNA) require early access to modern antiviral therapy.